IMPACT OF A RELATIONSHIP DEVELOPMENT GROUP ON STUDENTS’ INTERPERSONAL COMMUNICATION AND RELATIONSHIPS - Du Plooy, Kobus (South African Journal of Higher Education, 2016)
Together with the increasing pace of modern society and technological improvements, it appears that students’ psychological needs, complaints and methods of communication have also changed. At the University of Pretoria (UP) between January and October 2012 the most frequent problems presented at Division Student Support (DSS) were stress, anxiety and depression relating to academic, personal and particularly interpersonal relationships. Unsatisfactory interpersonal relationships appeared to have a detrimental impact on academic performance, which could culminate in the termination of studies. This highlighted the need for more effective psychotherapeutic interventions to improve communication and interpersonal relationships. Traditional psychotherapeutic approaches no longer appeared to be as effective. Increasing numbers of students suggested group intervention as opposed to individual psychotherapy. It was postulated that a semi-structured relationships development group (RDG) grounded in the inter-psychic approach could address the contemporary needs of students. Such a group of seven UP students was formed in April 2013. Initial findings based on the feedback from these group members show the semi-structured RDG to be an impactful and effective short-term psychotherapeutic tool to improve the quality of communication and interpersonal relationships of students at South African institutions of higher education. This would allow students who may be at risk of academically underperforming to improve their academic results and in doing so improve the academic success and throughput rates at South African institutions of higher education. Further research is advocated to verify these findings at other South African institutions of higher education.